James Monroe : diplomatic correspondence Paris, 1794-1796 - Monroe, James, 1758-1831 (Algora Publishing, 2021)
"This is the first time an editor has focused principally on James Monroe's written communications while serving as President George Washington's minister to France, a delicate and grueling service. The letters will interest a general readership as well as students of military, diplomatic, or political history; explanatory notes place the letters in their particular historical, political, or conceptual context"--